An analysis of the factors affecting cacao farmers' market channel choice in Calinan District, Davao City - Nuñeza, Jefferson G.
Highest satisfaction is what farmers want to achieve as they distribute their produce to the different market channels. This paper was conducted to determine the factors that cacao farmers in Calinan District consider in selling their harvested beans and evaluate the significance and relationships of each. In more specific terms, this study aims to provide comprehensive analysis on the connection between the choice of channels and the internal and external factors within the cacao industry. This is through identifying of the nodes of the supply chain, especially the market channels of the industry in Calinan District and the roles performed by each player, evaluating the factors that may affect and are considered by farmers. Six major market channels were identified in this study. These include Chinese Traders, Local Traders, Cooperatives, Regional Traders, Domestic Trader, Results for the qualitative analysis showed that majority of the farmers have been considering much the high price, the "suki" factor, strictness in quality, and the promptness of payment in choosing a market channel. Using the Multinomial Logit Model, quantitative results have shown that factors such as farm size, prices, production costs, and distance from farm to channel are significant in choosing Cooperative relative to Chinese Traders. Same results were found out in choosing Local Traders instead of Chinese traders except for farm size. Traders such as Regional Traders, Domestic Traders, and Exporters were omitted in the computation since these channels do not have an established buying station in the area.
Thesis, Undergraduate (BS Agribusiness Economics) -- U. P. Mindanao
Keywords: Cacao farmers -- Calinan, district(Davao City) -- Philippines -- Marketing channels